Coeliac disease, autoimmune thyroid disease and primary biliary cirrhosis: Case report - Erkan PARLAK; Perihan OĞUZ; Nurgül ŞAŞMAZ; Tülin ŞAHİN and Yasemin KOŞAR and Erdoğan KOVALI (Turkish Journal of Gastroenterology, 2019)
-